A 24-hour lighting scheme to promote alertness and circadian entrainment in railroad dispatchers on rotating shifts: A field study. (August 2022) - Sahin, L; Figueiro, MG
Shift-working railway personnel are highly susceptible to fatigue stemming from poor-quality sleep that can impair the performance of safety-critical functions. Disruption of the 24-h light–dark pattern incident on the retinae appears to play a central role in exacerbating these problems, especially with respect to exposure to light at night and circadian rhythms disruption. This field study tested and demonstrated the effectiveness and acceptability of an intervention (red and blue light combined with white light) to (1) promote circadian alignment, (2) advance the timing of dim light melatonin onset, (3) improve objective and subjective sleep quality, and (4) reduce subjective sleepiness in an operational context compared to a baseline (conventional lighting) condition. The lighting intervention promoted significantly greater synchrony between day-shift participants' light–dark exposures and rest–activity patterns, but did not significantly advance the timing of dim light melatonin onset. The intervention was also associated with reduced objective sleep disturbances and improved (albeit less robustly) subjective sleep quality, but it only reduced participants' subjective sleepiness while they were off duty during the day shift. This research demonstrates that lighting interventions can promote circadian alignment and improve sleep quality among railway shift workers and may be translatable to other 24-h industries.